Additional file 1 of Adherence to prescription guidelines and achievement of treatment goals among persons with coronary heart disease in Tromsø 7 - Elisabeth Pedersen (10021477); Beate Hennie Garcia (8976971); Kjell H. Halvorsen (8923601); Anne Elise Eggen (3808561); Henrik Schirmer (321882); Marit Waaseth (72811) (2021)
Additional file 1: Table S1. Overview of ATC-codes included in the three medication categories recommended for CHD based on the European Society of Cardiology: Guidelines on cardiovascular disease prevention in clinical practice (version 2012) [6]. Table S2. Variables included as covariates in propensity score. Table S3. Variables included in multiple imputation. Table S4. Achievement of treatment goal for HbA1c for participants with diabetes in the different CHD disease groups. Table S5. Results from propensity score matching of the ten imputed datasets for the logistic regression analysis of the association between use of lipid-lowering drugs and achieving the treatment goal for LDL-cholesterol. Table S6. Results from propensity score matching of the ten imputed datasets for the logistic regression analysis of the association between use of antihypertensive drugs and achieving the treatment goal for blood pressure among those with self-reported hypertension. Table S7. Pooled results from the sensitivity analysis for the logistic regression analyses of the multiple imputed datasets, using propensity score matching without replacement.